WAKAF NON MUSLIM DAN WAKAF UANG MENURUT PANDANGAN WAHBAH ZUHAILI - FITRA RIZAL (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
Islam presents itself as a philanthropic-faced religion, by realizing social security for the community to achieve a noble life. With the current development, it is important to bring up various challenges related to waqf law in Islam, specifically endowments, non-Muslims, and endowments of money. This article provides an explanation of how non-Muslim endowments and money waqf in Islam. According to Wahbah Zuhaili, Waqf from non-Muslims is permitted. Like in the activities of building mosques, schools and other facilities, both money, building materials and energy used for the construction. Donations or assistance are permitted, with conditions not binding and will not cause danger or slander in the future, both for Muslims and for supported institutions. According to Wahbah Zuhaili, waqf money is permissible. The Hanafi school that allows money waqf. For the reason of Istihsan bi al-Arabi, because many people have done it. In this regard, Wahbah Zuhaili states, in al-Fiqh al-Islamiy wa ill Adillatuhu, what is meant is generally as follows, "Mutaqodimiin of the Hanafi School allows waqf money and dinars".